Perfil e análise geoespacial do atendimento de doenças benignas mamárias em um país de dimensões continentais - Ferreira, Dayan Sansone [UNIFESP] (2020)
In Brazil, SUS serves more than 75 million women who do not have supplementary health care. Benign breast diseases (DBM) are common, with incidences reaching 20% ​​and possibly 50% in some cases. These diseases may be linked to an increased likelihood of developing breast cancer. The use of geospatial analysis tools can assist in strategic planning in public health management. This study used the databases of the Ministry of Health to survey medical care from 2008 to 2019 for DBM in all Brazilian municipalities. With these data it was analyzed what were the treatments and diagnoses of DBMs performed in each region of the country. Outpatient care (more than 4 million procedures performed in 12 years) were mostly diagnostic procedures, while treatments were mostly performed through hospitalizations (360,000 hospitalizations) and surgeries. The medical assistance provided by DBMs resulted in an expense of more than R $ 380 million over 12 years. Both the coverage of treatment and the displacement of the female population had differences between the regions of the country. The northern and central-western regions had different rates of coverage and displacement when compared to the other three regions of the country.